THE EFFECT OF PROFESSIONALISM IN VILLAGE ASSET MANAGEMENT, OPTIMIZATION OF THE VILLAGE ASSETS UTILIZATION AND COMMUNITY EMPOWERMENT ON INCREASING VILLAGE ORIGINAL INCOME IN KUALA SEMPANG VILLAGE, SERI KUALA LOBAM DISTRICT, BINTAN REGENCY - Mawarni, Mawarni; Ngaliman, Ngaliman; Satriawan, Bambang; Indrayani, Indrayani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine and describe how the influence of professionalism in managing village assets, optimizing the use of village assets and empowering the community so that it contributes to increasing village original income. The type of data used in this research is quantitative data. The data source in this research is secondary data. The object of this research is Kuala Sempang Village, Seri Kuala Lobam District, Bintan Regency. The results showed that the professionalism of village asset management had no significant effect on village original income, the optimization of the village assets utilization had a significant positive effect on village original income and community empowerment had no significant effect on village original income. So, in this study from the three variables only one variable has a significant positive effect on the village's original income.